PP67. PAEDIATRIC TECTAL PLATE ‘GLIOMAS’: A DECADE’S EXPERIENCE - Kalyal, Ms Nida (Neuro Oncol, 2017)
OBJECTIVE: Tectal plate ‘gliomas’ are uncommon, indolent lesions. Presentation is usually with hydrocephalus and diagnosis is typically made radiologically without histological confirmation. Long term data guiding management is lacking. METHOD: Retrospective review of all paediatric tectal plate lesions in our unit over the last 10 years. RESULTS: Fifteen patients (13 boys, 2 girls; mean age 8.9 years) were identified and included. Most presented with increased intracranial pressure. Fourteen patients (93%) had hydrocephalus at presentation. In 13 patients (87%) there was no progression of the lesion. CSF diversion was performed in 14 patients (93%). The initial intervention was endoscopic third ventriculostomy (ETV) in 12 (80%) and ventriculoperitoneal shunting in 3 (20%). Four patients (33%) were biopsied; 2 (17%) were WHO grade 1 pilocytic astrocytomas and 2 (17%) had non-diagnostic biopsies. Four patients (33%) received adjuvant therapy, two upfront (due to atypical radiological appearances) and 2 due to progression. Of the 4 patients receiving adjuvant therapy, 1 had chemotherapy only (Carboplatin and Vincristine), 1 had chemotherapy followed by proton beam therapy and 2 patients had focal radiation therapy (59.4 CGE). All patients were alive with stable disease at follow up (average 50.5 months; range 0–120 months). CONCLUSION: Our experience is in line with the published literature on the natural history of tectal plate ‘gliomas’ and supports the notion that these are low grade tumours that can be managed with cerebrospinal fluid diversion and surveillance imaging. Adjuvant therapy is reserved for progression and achieves long term control.